Impact of salvage treatment modalities in patients with positive FDG‐PET/CT after R‐CHOP chemotherapy for aggressive B‐cell non‐Hodgkin lymphoma. Issue 3 (25th March 2018) - Chin, Vicky; Fulham, Michael; Hertzberg, Mark; Jackson, Michael; Lindeman, Robert; Brighton, Timothy; Kidson‐Gerber, Giselle; Wegner, Eva A; Cheung, Carol; MacCallum, Susan; Williams, Janet; Thompson, Stephen R
Abstract: Introduction: To compare outcomes of different salvage treatment modalities in patients with aggressive B‐cell non‐Hodgkin lymphoma (NHL) who remain FDG‐PET positive after R‐CHOP chemotherapy. Existing data on these patients with FDG‐PET primary refractory disease are limited. Methods: Patients with diffuse large B‐cell lymphoma or grade 3 follicular lymphoma were retrospectively reviewed from the Prince of Wales Hospital databases. Eligibility criteria were: age≥18 years, treated with R‐CHOP, with positive post‐chemotherapy FDG‐PET. Salvage treatment modalities were: radical radiotherapy (RT, dose≥30 Gy), high dose chemotherapy and autologous stem cell transplant (ASCT), or non‐radical management. Survival was calculated from date of post‐chemotherapy FDG‐PET to last follow‐up. Results: Twenty‐six patients from 2003–2015 met the inclusion criteria. Median age was 60 (range 19–84). Most had adverse baseline features: 21 (81%) stage III‐IV, 24 (92%) bulky disease and nine (35%) skeletal involvement. Characteristics of PET‐positivity post‐chemotherapy were single site in 16 (62%), sites of prior bulk in 24 of 24, skeletal sites in five of nine, and able to be encompassed by RT in 21 (81%). Salvage treatment was: radical RT in 17 (65%), ASCT in four (15%) and non‐radical in five (20%). Median follow‐up of surviving patients was 31 months. Kaplan–Meier estimates of 3‐year PFS and OS were 41% and 52%, respectively. By salvage modality, 3‐year PFS was 51% for RT, 25% for ASCT and 20% for non‐radical treatment, ( P  =   0.453); 3‐year OS was respectively 65%, 25% and 40% ( P  =   0.173). Conclusion: Patients with FDG‐PET positive disease after R‐CHOP for aggressive B‐cell NHL are salvageable with radiotherapy.